Effect of harvesting time on quality and shelf-life of three ‘Galia’ cultivars - Baraka, Al Fadil; Abu-Goukh, Abu-Bakr; Elballa, Mustafa (Gezira Journal of Agricultural Science; Vol 13 No 1 (2015), 2015)
Two harvesting maturities in the boarder-line of physiological maturity of three ‘Galia’ cultivars (41 and 44 days after anthesis, DAA) were evaluated during the winter season (2008/2009) at Silate Agricultural Scheme, with respect to quality and shelf-life of the fruits at 18 ± 1 o C and  85-90% relative humidity. The cultivars studied were ‘Galia’ F 1 Standard, ‘Galia’ F 1 MN-318 and ‘Galia’ F 1 Solar King. The respiration curves of the three cultivars exhibited a typical climacteric pattern of respiration at both harvesting maturities. Fruits harvested slightly immature (41 DAA), had a lower respiration rate at harvest and during the pre-climacteric phase and higher rates during the post-climacteric phase, compared to those harvested at physiological maturity (44 DAA). Although the fruits harvested at physiological maturity (44 DAA) ripened normally, those harvested slightly immature (41 DAA) failed to develop rind color, to soften, to accumulate TSS or to develop flavor during ripening. At the end of the ripening period, the fruits picked 44 DAA reached the full yellow color (color score 6), while those picked 41 DAA had only reached an average of 2.3 color score. At the full ripe stage, TSS accumulation reached an average of 12.2% in fruits harvested 44 DAA, compared to only 8.8% in those harvested 41 DAA. The drop in fruit flesh firmness during the course of ripening was about 94% in fruits picked 44 DAA and only 33% in fruits picked 41 DAA. The fruits harvested 44 DAA developed excellent flavor (score 5), but those harvested 41 DAA failed to develop flavor. ‘Galia’ cantaloupes should be harvested at the physiological maturity, which corresponds to a change in rind color from green to yellow at the stem-end and with complete netting and formation of the abscission layer. تم تقويم وقت الحصاد في درجتين على حافة اكتمال النمو الفسيولوجي (41 و44 يوماً من تفتح الأزهار في مشروع السليت أثناء الموسم الشتوي (2008/2009)، فيما يختص بالجودة والعمر التسويقي لثمار ثلاثة أصناف من شمام ’القاليا’ عند درجة حرارة 18±1º ورطوبة نسبية 85-90 %. كانت الأصناف الثلاثة التي أجريت الدراسة عليها هي، (Galia F 1 Standard)و (Galia F 1 MN-318) و(Galia F 1 Solar King). اتبعت الثمار على مستوى درجتي اكتمال النمو في تنفسها نمط التنفس الكلايماكتيرى في الأصناف الثلاثة. وكان تنفس الثمار التي حصدت قبيل اكتمال النمو الفسيولوجي (41 يوماً من تفتح الأزهار) منخفضاً نسبياً عند الحصاد وأثناء مرحلة ما قبل ذروة التنفس وأعلى نسبياً أثناء مرحلة ما بعد ذروة التنفس، مقارنة بالثمار التي حصدت في مرحلة اكتمال النمو الفسيولوجي ( 44 يوماً من تفتح الأزهار). بالرغم من أن الثمار التي حصدت مكتملة النمو فسيولوجياً (44 يوماً من الإزهار) قد نضجت بصورة طبيعية، إلا أن الثمار التي حصدت قبيل اكتمال النمو الفسيولوجي (41 يوماً من الإزهار) قد فشلت في أن تتلون قشرتها ويلين لبها وتتجمع المواد الصلبة الذائبة الكلية فيها وتتطور النكهة فيها أثناء النضج. عند نهاية فترة النضج وصل لون قشرة الثمار التي قطفت بعد 44 يوماً من الإزهار إلى اللون الأصفر الكامل (معدل 6 نقاط) بينما لم يزد معدل تلون قشرة الثمار التي قطفت بعد 41 يوماً من الإزهار عن معدل اللون 2.3نقطة. في مرحلة النضج الكامل وصل متوسط مقدار المواد الصلبة الذائبة الكلية المتراكمة 12.2% في الثمار التي حصدت بعد 44 يوماً من الإزهار، مقارنة ب 8.8% فقط في تلك التي حصدت بعد 41 يوماً من الإزهار. بلغ الانخفاض في صلابة الثمار أثناء نضجها 94% في الثمار التي قطفت بعد 44 يوماً من الإزهار و لم يتجاوز نسبة 33% في الثمار التي قطفت بعد 41 يوماً من الإزهار. وصلت النكهة في الثمار المكتملة النمو فسيولوجياً (44 يوماً من الإزهار) درجة الامتياز (5 درجات)، ولم تتكون النكهة في الثمار التي حصدت بعد 41 يوماً من الإزهار. يجب حصاد ثمار شمام القاليا عند مرحلة اكتمال النمو الفسيولوجي، والتي تتوافق مع تغيير لون قشرة الثمار بالطرف الساقي من الأخضر إلى الأصفر، واكتمال التكوين الشبكي عليها، وتكوين طبقة الانفصال بين الثمرة والفرع الحامل لها.